Effects of type II collagen epitope carbamylation and citrullination in human leucocyte antigen (HLA)‐DR4+ monozygotic twins discordant for rheumatoid arthritis. (25th July 2016) - De Santis, M.; Ceribelli, A.; Cavaciocchi, F.; Generali, E.; Massarotti, M.; Isailovic, N.; Crotti, C.; Scherer, H. U.; Montecucco, C.; Selmi, C.
Summary: The aim of this study is to investigate the effect of the native, citrullinated or carbamylated type II human collagen T cell‐ and B cell‐epitopes on the adaptive immune response in rheumatoid arthritis (RA). Peripheral blood T and B cells obtained from a human leucocyte D4‐related (antigen DR4 − HLA‐DR4) + woman with early RA, her healthy monozygotic twin and an unrelated HLA‐DR3 + woman with early RA were analysed for activation (CD154/CD69), apoptosis (annexin/7‐aminoactinomycin), cytokine production [interferon (IFN)γ/interleukin (IL)−17/IL‐4/IL‐10/IL‐6] and functional phenotype (CD45Ra/CCR7) after stimulation with the collagen native T cell epitope (T261‐273), the K264 carbamylated T cell epitope (carT261–273), the native B cell epitope (B359–369) or the R360 citrullinated B cell epitope (citB359–369), and the combinations of these. The T cell memory compartment was activated by T cell epitopes in both discordant DR4 + twins, but not in the DR3 + RA. The collagen‐specific activation of CD4 + T cells was induced with both the native and carbamylated T cell epitopes only in the RA twin. Both T cell epitopes also induced IL‐17 production in the RA twin, but a greater IL‐4 and IL‐10 response in the healthy twin. The citrullinated B cell epitope, particularly when combined with the carbamylated T cell epitope, induced B cell activation and an increased IL‐6/IL‐10 ratio in the RA twin compared to a greater IL‐10 production in the healthy twin. Our data suggest that circulating collagen‐specific T and B cells are found in HLA‐DR4 + subjects, but only RA activated cells express co‐stimulatory molecules and produce proinflammatory cytokines. Carbamylation and citrullination further modulate the activation and cytokine polarization of T and B cells.